Martinetti e Banfi tra teoria e prassi (Materiali di Estetica. Terza serie, 2022)
The Martinetti-Banfi relationship was investigated by critics, who identified the point of origin of the Milan School in the Banfi work. Yet, if the texts are analyzed, it is not difficult to find a continuity between teacher and pupil. If this seems evident in the first Banfi writings, the more markedly theoretical ones, even the more mature Banfi production seems indebted to Martinetti's origins. Both in the confrontation with phenomenology and with Marxism, Banfi insists on Martinetti's attempt to reconcile the dualisms characteristic of the metaphysical tradition. In this continuity, elements of discontinuity also emerge, starting with a growing materialism absent in Martinetti's spiritualism
Keywords: Teacher; Pupil; Continuity; Transcendence; Immanence; Dualism; Modernity